Wide temperature enhanced sodium storage in tailored, sustainable sodiophilic biphasic N-doped carbon - Yadav, Poonam; Das, Anoushka K.; Torris, Arun; Wasnik, Kundan; Koppisetti, Heramba Venkata Sai Rama Murthy; Pol, Vilas G.; Shelke, Vilas; Shelke, Manjusha (Materials Today Chemistry, 2024)
Alternative to Li-ion batteries(LIB), Na-ion batteries (NIB) and Na metal batteries (NMB) are gaining significant attention due to their low cost, abundance, and safety. By modulating microstructural properties such as graphitization, heteroatom doping, surface-rich functional groups, and interlayer d-spacing, Na-ion storage in NIB and Na plating/striping in NMB can be ameliorated. This study reports sodiophilic N-doped polymer-derived carbon (PDC) as an anode for NIB and host for Na metal in NMB. As NIB anode, PDC provides a storage capacity of 173 mAh g- 1 at 1 A g- 1 in half-cell and 84 mAh g- 1 at 1C (1C = 128 mAhg- 1) in full-cell with Na3V2(PO4)2F3 (NVPF) cathode. As Na metal anode (NMA) host, a high columbic efficiency (C.E.) of 99.45% for over 1000 cycles at 6 mA cm- 2_4 mAh cm-2 is obtained. Furthermore, fascinating wide temperature (50 degrees C and -20 degrees C) sodiumion storage is successfully demonstrated by PDC. Advanced X-ray photoelectron spectroscopy (XPS) confirmed the formation of stable and uniform solid electrolyte interphase (SEI) composed of inorganic and organic components, X-ray microtomography confirmed uniform Na plating throughout the volume of the electrode analogous to Brunauer-Emmett-Teller (BET) surface area, Raman spectroscopy, X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) results. A sustainable and scalable promising biphasic NIB anode and sodiophilic host for Na metal was possible due to larger d-spacing, partial graphitization, high mesoporosity, N-doping, presence of surface functional groups, better charge transfer, and diffusion properties.
Keywords: Full-cell; Low and elevated temperatures; Na metal host; Polymer-derived carbon; Sodium-ion battery; X-ray tomography

In situ solid-state synthesis of nitrogen-enriched porous carbon nanosheets from petroleum coke for lithium-ion hybrid capacitors - Benoy, Santhi Maria; Das, Anoushka K.; Sarmah, Debashis; Pawar, Meenakshi; Shelke, Manjusha V.; Saikia, Binoy K. (Energy & Fuels, 2025)
Lithium-ion capacitors (LICs) have emerged as a next-generation energy storage technology, offering a unique balance between the high energy density of lithium-ion batteries and the fast charge-discharge capability of supercapacitors. However, the development of high-performance anode materials remains a major challenge due to the trade-off between capacity, rate capability, and long-term cycling stability. Herein, we report a novel in situ solid-state synthesis approach for the scalable production of nitrogen-enriched porous carbon nanosheets (mBG1) from petroleum coke, an abundant industrial byproduct. The hierarchical porosity and optimized nitrogen functionalities of mBG1 facilitate rapid lithium-ion diffusion, enhanced electronic conductivity, and robust structural stability. Electrochemical characterization in lithium-ion half-cells demonstrates an exceptional specific capacity of 388 mAh g-1 at 0.1 A g-1, with an outstanding capacity retention of 92.7% over 1000 cycles (261.2 mAh g-1) at 1 A g-1. To validate its practical applicability, a full LIC coin cell was fabricated using mBG1 as the anode and commercial super activated carbon (super AC) as the cathode, achieving a specific capacitance of 44 F g-1 at 1 A g-1, a high energy density of 93.29 Wh kg-1 at 0.5 A g-1, and an impressive power density of 20.34 kW kg-1 at 10 A g-1, with 74% capacitance retention after 5000 cycles. The integration of ultrahigh nitrogen doping, hierarchical porosity, and scalable synthesis techniques offers a new pathway for designing next-generation lithium-ion capacitors with enhanced efficiency, stability, and economic viability. These findings establish mBG1 as a high-performance, scalable, and sustainable anode material for next-generation LICs, offering a transformative pathway for the valorization of petroleum coke in advanced energy storage applications.

Methoxyl-containing hyper-crosslinked polymer from largely bio-based biphenyl methyl ether and its application in lithium-sulfur battery - Wale, Apparav K.; Das, Anoushka K.; Patil, Nita R.; Shelke, V. Manjusha; Ambade, V. Ashootosh; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2025)
A new biphenyl methyl ether viz 2,2 `,3,3 `-tetramethoxy-5,5 `-bis(methoxymethyl)-1,1 `-biphenyl (TBMB) was synthesized starting from vanillin via three-step reaction sequence. The self-polycondensation of TBMB by employing two Bronsted acid catalysts, viz, p- toluenesulfonic acid (PTSA) and trifluoromethanesulfonic acid (TFSA) led to the formation of organic hyper-crosslinked polymers (HCPs) containing built-in methoxyl groups. HCPs were characterized by FTIR, solid state 13 C NMR, XPS, XRD, TGA, BET, and FESEM analysis techniques. HCPs synthesized using PTSA (HCP-PTSA) and TFSA (HCP-TFSA) exhibited a Brunauer-Emmett-Teller (BET) surface area of 480 +/- 5 and 590 +/- 4 m2/g, respectively and consisted of hierarchical pore structures with both micropores and mesopores. HCP-TFSA was evaluated as an active coating layer on conventional polypropylene (PP) separator in lithium-sulfur batteries to suppress the polysulfide shuttling on account of the ability of methoxyl groups to anchor soluble polysulfide species via coordination. The significant polysulfide adsorption capacity and improved cycling stability with a capacity of 617.2 mAh g- 1 at 0.5C and 99% capacity retention highlighted the potential of porous HCP containing built-in methoxyl groups in the development of attractive lithium-sulfur battery systems.
Keywords: Active coating layer; bio-based; Biphenyl methyl ether; Hyper-crosslinked polymer; lithium-sulfur battery; Methoxyl groups; Self-polycondensation

Unlocking enhanced redox dynamics: the power of a bifunctional catalytic zinc phosphide interface in full cell and pouch lithium-sulfur batteries - Das, Anoushka K.; Yadav, Poonam; Verma, Tushar S.; Marulasiddappa, Thripuranthaka; Krishnamurty, Sailaja; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Lithium-sulfur (Li-S) batteries face significant challenges, such as polysulfide dissolution, sluggish reaction kinetics, and lithium anode corrosion, hindering their practical application. Herein, we report a highly effective approach using a zinc phosphide (ZnP2) bifunctional catalyst to address these issues. The ZnP2 catalyst effectively anchors lithium polysulfides (LiPSs), catalytically reactivates them, and enhances lithium-ion diffusion. Utilizing a ZnP2-modified separator in a Li-S half-cell achieves an impressive initial capacity of 1145.4 mAh g-1, retaining 954 mAh g-1 and 99.8% Coulombic efficiency after 100 cycles, compared to the pristine separator. The underlying reaction mechanisms are thoroughly investigated through post-mortem analyses and density functional theory (DFT) calculations. Moreover, a Li-S full cell with an E/S ratio of 10 mu L mg-1 demonstrates stable cycling performance, achieving an initial capacity of 797.5 and 534 mAh g-1 after 100 cycles at 0.1C, with a negative-to-positive mass ratio of 3:1. Additionally, the real-world feasibility of lightweight and flexible Li-S pouch batteries with ZnP2-modified separators is explored, showing a stable performance over 100 cycles at 0.1C with 80% capacity retention. This engineered separator can be integrated with advanced sulfur cathodes to create high-energy-density, stable Li-S batteries for commercial applications.
Keywords: catalytic interlayer; full cell; lithium dendrite; lithium sulfur battery; polysulfide shuttling; pouchcell